2012
DOI: 10.1590/s0101-31222012000200001
|View full text |Cite
|
Sign up to set email alerts
|

The use of film coating on the performance of treated corn seed

Abstract: -The main objective of seed coating technology using polymers is to improve the physical, physiological and sanitary characteristics of seed performance. The objectives of the present study were to determine: the plantability of corn seeds treated with insecticide, fungicide and graphite, covered with a film coating; the dust retention on treated corn seeds; and the leaching of applied products on corn seeds covered by a film coating. Seed plantability was determined by counting the skips and double seeds; dus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 9 publications
1
34
0
1
Order By: Relevance
“…Leaching is prevented to a greater extent by the presence of more organic matter (BROZNIĆ et al, 2012;ROY et al, 2014). Avelar et al (2012) observed that maize seeds coated with the PolySeed CF polymer had five times more efficiency in the retention of Furazin 310 TS® insecticide containing 210 g zinc L -1 , used for the treatment of seeds. Of the insecticides compared to seeds that did not receive polymers, quantified by the amount of zinc extracted in 100 cm 3 of sand after a 50 mm precipitation; however the other polymer used Color Seed C3, was not efficient in the insecticide retention, because the zinc was leached up to twice as much as the treatment with insecticide alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaching is prevented to a greater extent by the presence of more organic matter (BROZNIĆ et al, 2012;ROY et al, 2014). Avelar et al (2012) observed that maize seeds coated with the PolySeed CF polymer had five times more efficiency in the retention of Furazin 310 TS® insecticide containing 210 g zinc L -1 , used for the treatment of seeds. Of the insecticides compared to seeds that did not receive polymers, quantified by the amount of zinc extracted in 100 cm 3 of sand after a 50 mm precipitation; however the other polymer used Color Seed C3, was not efficient in the insecticide retention, because the zinc was leached up to twice as much as the treatment with insecticide alone.…”
Section: Resultsmentioning
confidence: 99%
“…Of the insecticides compared to seeds that did not receive polymers, quantified by the amount of zinc extracted in 100 cm 3 of sand after a 50 mm precipitation; however the other polymer used Color Seed C3, was not efficient in the insecticide retention, because the zinc was leached up to twice as much as the treatment with insecticide alone. The authors (AVELAR et al, 2012) attributed these results to the lack of compatibility and low adhesion of the Color Seed C3 polymer and the insecticide used in the treatment. Similarly in this work, the Florite 1127® polymer (Tables 4 and 5) may have presented incompatibility and lack of adherence to the insecticide thiamethoxam, since it was inefficient in retaining the insecticide with the seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported satisfactory effects of seed coating on seed germination, seedling growth, root and shoot growth, leaf area, dry biomass and increase in yield (Zelonka et al, 2005;Gevrek et al, 2012;Tavares et al, 2012;Tavares et al, 2013). In addition, seed coating improves plantability, reduces the percentage of skips and doubles, reduces the formation of dust from seed and minimizes the leaching of insecticide from treated seed (Avelar et al, 2012). Accordingly, the objective of this study was to evaluate the effect on the seed quality and seedling performance of barley resulting from seed coating with various combinations of calcium, silicon, polymer and fungicide.…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, the use of zinc has been associated with improvements in seed vigor and germination (Ribeiro and Santos, 1996), once this micronutrient acts as an enzymatic activator in lipids and proteins metabolic pathways (Prado et al, 2007). Furthermore, coat adding a polymer to form a thin layer on the seed surface allows better distribution of active ingredients (Baudet and Peres, 2004), reduce the amount of chemicals used (Karam et al, 2007) and minimize the leaching of these products from treated seeds (Avelar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%